PERILAKU POLITIK MASYARAKAT PESISIR DALAM PEMILIHAN KEPALA DAERAH DI PULAU MARINGKIK, LOMBOK TIMUR - Nurun Sholeh; Abdurrohman Abdurrohman; Lalu M. Istiqlal; Zulkarnain Zulkarnain (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2025)
This study aims to inform the public about the political behavior of communities in remote areas, specifically the people of Maringkik Island. The main objective is to uncover the political behavior of the Maringkik Island community during the 2024 East Lombok Regional Head Election (Pilkada). This is a qualitative research using a case study approach. Data were collected through observation, interviews, and document analysis. Data analysis was conducted through five stages: compiling & organizing data, disassembling, interpreting, concluding, and verifyng .The findings reveal that in facing the 2024 East Lombok Pilkada, the people of Maringkik Island were more engaged in their daily routines as fishermen. They were largely unaffected by the political commotion surrounding the election. Although candidates and their campaign teams visited the island with promises of improving the residents’ quality of life. Coastal residents of Maringkik Island hold the perception that local elections have never brought substantial or positive changes to their socio-economic conditions. This perception shapes a political behavior that tends to be passive and apolitical. Nevertheless, they still participate in the election, although their choices are often based on pragmatic and emotional considerations. Ultimately, the people of Maringkik Island prioritize social harmony and maintaining strong social bonds over political differences. This reflects a political orientation that values social cohesion more than active involvement in electoral politics.